Factors influencing the financial sustainability of the non-profit sector in South Africa - Harding, Joanne (Department of Social Development, 2014)
This study explored the financial sustainability of NPOs within the South African context, post the 2008 economic crisis. The overall aim was to understand the factors which affect NPOs ability to financially sustain themselves. Trends of NPO income and expenditure were analysed and measures taken to address changes in the financial situation examined. The study explored different funding agencies and their role in supporting NPOs. Lastly, perceptions of governance, funding practice, and current situations in organisations were explored and recommendations made for the future. A quantitative methodology was adopted using the online survey tool Survey Gizmo. Secondary data in the form of financial statements were requested from NPOs. The Inyathelo data base of organisations made up the population of 469 organisations and responses were received from 101 organisations. This was a satisfactory 21,5% response rate. Data was analysed by calculating descriptive statistics. These were represented in a narrative and visually in the form of graphs and tables. Financial data was captured and analysed in order to corroborate the data. The research found that income to NPOs is not increasing to keep up with inflation. Demand for NPO services has increased due to the global economic crisis and as a result NPOs experience increasing pressure on their financial resources. NPOs are perceived to be critical to the well being of society but the sector is under pressure, with many showing a financial deficit. The sector is looking to government and corporates to help strengthen it, but are also wanting to become less dependent on external sources for their financial sustainability. NPOs are of the opinion that they need to find new strategies to ensure their sustainability. The following are key recommendations: NPOs must be creative about managing increased demand for their services;; NPOs should collaborate to advocate for changes in relationships with major financial contributors and work together to promote philanthropy in the country;; funders should adjust their funding models in order to strengthen the NPO sector while still focussing on the needs of beneficiaries.